Diversity, inclusion, and equity in Qatar’s K-12 schools: exploring strategic approaches for recruitment, development, and retention - Al-Kubaisi, Huda (Frontiers in Education, 2024)
This critical review study aimed to thoroughly evaluate methods for fostering principles of diversity, inclusion, and equity in the hiring, training, and retention processes of educators in Qatar’s schools. It incorporated the analysis of existing policies and practices, and the identification of gaps to propose evidence-based methods that likely enhance the three principles among educators. It also sought to provide additional knowledge and potential solutions that may significantly improve them. Further, I studied effective methods for enlisting educators from varied backgrounds, considering cultural, linguistic, and other relevant considerations, to satisfy the urgent demand for diversity among educators. Examining the importance of professional development programs in this context was crucial in encouraging inclusion and equity. Many institutional, cultural, and systemic impediments to progress have been revealed. The findings underline the significance of having a diverse educational workforce to foster inclusive and equitable educational experiences for students in schools in Qatar. They also emphasize the necessity for ongoing collaboration among stakeholders to achieve this goal. In response, legislative amendments, specialized recruitment strategies, professional development initiatives, and support systems are proposed to effectively address these challenges. Therefore, this research contributes to the scholarly discourse on diversity, inclusivity, and equity in education.